Firm location, Corporate Structure, R&D Investment, Innovation and Productivity - Börje Johansson; Hans Lööf; Amy Rade Olsson (European Regional Science Association (ERSA), 2005)
This study elucidates the relationship between localisation of firms, corporate structure, intellectual capital and innovations.The main finding is that a greater concentration of multinational firms, human capital, T&D and universities is significantly and positive associated with research productivity. All other things equal, such as firm size, sector classification, human capital, corporate owner structure and R&D investment, the return to an invested Euro in R&D is, at the margin, greatest for firms localized to the capital of Sweden, compared to four other large regions. However, surprisingly Stockholm firms also have a lower propensity to cooperate with scientific, vertical and horisontal innovation systems. This may reflect limitations of popular survey-based information such as Community Innovation Survey data to capture spillover and the importance of informal collaborative relationships within regions.
Keywords: 330